Psychological and pedagogical conditions for the effective formation of imaginative thinking among students of Art - Almaz, Nurazkhan; Daulet, Kabylov; Manifa, Sarkulova; Amrekul, Abuov; Ulbossyn, Aimbetova (International Journal of Psychosocial Rehabilitation, 2020)
Fine art is part of artistic creation. An important component of it is folk decorative art and portraiture and has great pedagogical potential. It is more accessible to students than the results of the work of professional artists. Things-works related to the art in question are widely represented in a man-made environment. They reflect the high moral ideals and high aesthetic taste of the authors harmoniously combine the necessary utilitarianism and the perfection of the art form, embody incredible industriousness and magnificent possession of the beauty of the material and so on. Students often meet with them in everyday life. For this reason, works of this art have a significant impact on the formation of the student’s personality.